2023
DOI: 10.11002/kjfp.2023.30.3.526
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Allium ochotense Prokh. extract against ethanol-induced cytotoxicity

Abstract: This study aimed to evaluate the antioxidant and hepatoprotective effects of aqueous and 60% ethanol extracts of Allium ochotense Prokh. against alcohol-induced cytotoxicity as well as on the activities of alcohol-metabolic enzymes. Antioxidant effects of the extracts were analyzed using 3-ethylbenzothiazoline-6-sulfonic acid, 1,1-diphenyl-2-picrylhydrazl, ferric reducing antioxidant power, and malondialdehyde a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Contrary to such reports, knowledge regarding the mechanism of the protective effect of A. ochotense extract against alcohol-induced liver toxicity is limited. Findings from our previous study confirmed the in vitro antioxidant and cytoprotective effects of A. ochotense extract against ethanol-induced hepatocyte toxicity using A. ochotense extract [11]. Based on these preliminary findings, A. ochotense extract was used in this study to examine the mechanism of the effect of improvement of lipid metabolism disorders and alcoholic hepatitis in the liver of alcohol-induced experimental animals.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…Contrary to such reports, knowledge regarding the mechanism of the protective effect of A. ochotense extract against alcohol-induced liver toxicity is limited. Findings from our previous study confirmed the in vitro antioxidant and cytoprotective effects of A. ochotense extract against ethanol-induced hepatocyte toxicity using A. ochotense extract [11]. Based on these preliminary findings, A. ochotense extract was used in this study to examine the mechanism of the effect of improvement of lipid metabolism disorders and alcoholic hepatitis in the liver of alcohol-induced experimental animals.…”
Section: Introductionsupporting
confidence: 68%
“…A. ochotense leaves have been reported to be rich in flavonoids including kaempferol, quercetin, and astragalin, as well as phenolic compounds such as ferulic acid [11]. Kestose and raffinose, kaempferol di-glucoside isomer, quercetin glucoside isomer, and kaempferol glucoside isomer have also been identified in EA (Figure 2 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations